2022
DOI: 10.1002/adfm.202112540
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Component Crosslinked Hydrogel Electrolyte toward Dendrite‐Free Aqueous Zn Ion Batteries with High Temperature Adaptability

Abstract: Rechargeable aqueous Zn‐ion batteries (ZIBs) are always regarded as a promising energy storage device owing to their higher safety and durability. However, two problems have become the main trouble for the practical application of ZIBs such as the dendrite growth of Zn metal anode in electrolyte and the freezing of water solvent at low temperature. Herein, to overcome these challenges, a new strategy, multi‐component crosslinked hydrogel electrolyte, is proposed to inhibit Zn dendrites and realize low temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(106 citation statements)
references
References 59 publications
1
104
1
Order By: Relevance
“…Even worse, voltage gaps of Zn|LE|Cu and Zn|PAMHE|Cu cells increase gradually as the cycles rise, verifying the continuous dendritic Zn growth. [51,52] It is reasonably concluded that the PASHE can effectively improve the reversibility of Zn plating/ stripping owing to its positive effect on suppressing dendrite and parasitic reactions, as evidenced by SEM results and optical photographs. After cycling, Zn and Cu foils of Zn|LE|Cu (Figure S8a,d, Supporting Information) and Zn|PAMHE|Cu (Figure S8b,e, Supporting Information) cells show scattered dark Zn deposition spots with sharp tip morphologies.…”
Section: Resultsmentioning
confidence: 89%
“…Even worse, voltage gaps of Zn|LE|Cu and Zn|PAMHE|Cu cells increase gradually as the cycles rise, verifying the continuous dendritic Zn growth. [51,52] It is reasonably concluded that the PASHE can effectively improve the reversibility of Zn plating/ stripping owing to its positive effect on suppressing dendrite and parasitic reactions, as evidenced by SEM results and optical photographs. After cycling, Zn and Cu foils of Zn|LE|Cu (Figure S8a,d, Supporting Information) and Zn|PAMHE|Cu (Figure S8b,e, Supporting Information) cells show scattered dark Zn deposition spots with sharp tip morphologies.…”
Section: Resultsmentioning
confidence: 89%
“…[39] In addition, the ex situ X-ray photoelectron spectroscopy analysis also confirms the excellent reversibility of the Zn@CuHCF//V 2 O 5 full cell (Figure S24, Supporting Information). [22,63,65] Moreover, the Zn@CuHCF// V 2 O 5 full battery delivers an excellent reversible discharge capacity of 100.8 mAh g -1 with the capacity retention of 87.6% after 3000 cycles at 10 A g -1 , and the bare Zn//V 2 O 5 full cell has a rapid capacity attenuation after being fully activated and the capacity retention rate of only 32.9% is obtained (Figure 4d). It can be observed that the SEM image of the Zn@CuHCF anode surface is still flat after 500 cycles at 10 A g -1 , while the surface of the bare Zn anode shows obvious uneven Zn dendrite growth (Figure S25, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Besides, the water-in-salt electrolyte and gel-based quasi-solid electrolyte can be also acted as water-starved electrolytes to achieve high-performance Zn metal anode. [12,[20][21][22] It has been noted that dendrite growth and side reactions mainly occur at the contact surface between the bulk aqueous electrolyte and Zn metal electrode, thus constructing an effective interface protection layer cannot only reduce the risk of short-circuit, but also decrease the adverse effects of water contact with the electrode. [13] Meantime, designing an artificial coating layer to restrict the dendrite growth is necessary due to its simplicity, adjustable thickness, and low cost.…”
Section: Research Articlementioning
confidence: 99%
“…However, the tightly connected networks in PVA made it less absorptive to liquid electrolytes, which caused low ionic conductivity. 62 Through cross-linking, 63 heat treatment 64 and compounding with other materials, 65 the mechanical properties and absorption capacity of PVA can be enhanced.…”
Section: The Types and Characterization Methods Of Gpesmentioning
confidence: 99%